Factors predicting self-protective behaviors against PM2.5 exposure among rural community-dwelling older adults in the Central Region of Thailand: A cross-sectional study - Winthanyou Bunthan; Anchalee Ngamchantratip; Pirunlak Jitdorn; Jariyawat Kompayak (Journal of Public Health and Development, 2026)
Health problems resulting from exposure to Particulate Matter 2.5 (PM2.5) have been increasing rapidly, especially among vulnerable groups such as older adults. This cross-sectional survey research aimed to examine the level of self-protective behaviors and the factors predicting such behaviors against PM2.5 exposure among 885 rural community-dwelling older adults in the central region of Thailand. The research instruments consisted of three parts: 1) a demographic questionnaire for older adults including related modifying factors; 2) a questionnaire assessing predictive factors based on the six-dimension Health Belief Model, including perceived risk of health problems, perceived severity of health problems, perceived benefits of self-protection, perceived barriers to self-protection, perceived self-efficacy, and perceived cues to action; and 3) a questionnaire on self-protective behaviors against PM2.5 exposure. The data were analyzed using descriptive statistics and stepwise multiple regression analysis. The results revealed that the mean score for overall self-protective behaviors against PM2.5 exposure among Thai rural community-dwelling older adults was at a good level (µ = 2.23, σ = 0.61). Factors based on the Health Belief Model, including age, perceived benefits of prevention, perceived barriers to prevention, perceived self-efficacy, and perceived cues to action, jointly predicted self-protective behaviors against PM2.5 exposure, accounting for 57.00% of the variance, with statistical significance at .05 (R² = .570, p < .001). Based on the findings, healthcare providers should incorporate these predictive factors when designing interventions aimed at modifying health behaviors to effectively prevent health problems and diseases caused by PM2.5 exposure among Thai rural community-dwelling older adults.